Предмет: Алгебра,
автор: sundovadarya
решение плиз на этот пример срочно! (3x - 2) (3x+2) - (3x - 1) ( 3x+3) = 5
Ответы
Автор ответа:
0
9х^2+6х-6х-4-9х^2-6х-3=5
-6х-7=5
-6х=12
х=-2
-6х-7=5
-6х=12
х=-2
Автор ответа:
0
(3x)² - 2² - 3(3x - 1)(x + 1) - 5 = 0
9x² - 4 - 3(3x² + 3x - x -1) - 5 = 0
9x² - 4 - 9x² - 9x + 3x + 3 - 5 = 0
-6x - 6 = 0
-6x = 6
x = 6 / (-6)
x = -1
9x² - 4 - 3(3x² + 3x - x -1) - 5 = 0
9x² - 4 - 9x² - 9x + 3x + 3 - 5 = 0
-6x - 6 = 0
-6x = 6
x = 6 / (-6)
x = -1
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: brabokon7
Предмет: Математика,
автор: jeonchaeyongjkkkkk
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: nasta060502